Islamic insurance model revisited: operationalizing the business paradigm within the shari'ah parameters / Fatima Abdelwahab Galal - Abdelwahab Galal, Fatima (2015)
This thesis revisited the Islamic insurance models' operations and its various business paradigms within the Shari'ah parameters in three different countries which are Bahrain, Malaysia, and Sudan. Although, the Islamic insurance industry is experiencing a period of rapid growth in terms of its net contributions and profit, amidst tough obstacles and constraints due to the Shar'iah issues in certain aspects. Islamic insurance operations require fine-tuning in line with Islamic jurisprudence and Muslims need. There are many different operational models with various Islamic jurisdictions trying to meet the needs of Muslims in general as regard Islamic insurance in the global Islamic economy. However, each of these models has its own advantages and disadvantages. Moreover, there is no agreement amongst the Islamic scholars on which of these models can be considered the best. This means different organizations use the same Islamic contract but with different applications. These models, which are Wakalah, Mudarabah, Waqafmd the Hybrid model, have several shortcomings that need to be studied and addressed to strengthen global Islamic insurance industry. The two challenging issues that are studied are the ownership of the Islamic insurance risk fund or the contribution fund and the surplus distribution accumulated from the risk fund. There are differences of opinion regarding Shari'ah compliance of certain practices. This has led to layers of regulatory differences in countries like Bahrain, Malaysia, and Sudan, resulting in initiation of separate regulatory frameworks for Islamic insurance as a medium to ensure rapid growth and encourage Islamic insurance. This study adopts MANOVA because there are multiple dependent variables as well as independent variables within the constructs of the research. The first objective illustrates a well-structured understanding of the insurance principle practiced in Islamic insurance. MANOVA was conducted to test for substantial differences in the application of insurance principles in the operation of Islamic insurance within the selected countries. Moreover, the second objective examines the association between Shari'ah rules and some items in the business operation of Islamic insurance in the selected countries that operate Islamic Insurance. Furthermore, the objective three investigates the similarities and differences in the running of Islamic insurance business in selected countries. On the other hand, objective four addresses the justification of Islamic insurers on their selected operational models and this segment concludes with the last objective that proposes an operational model that will be acceptable to all Islamic insurance companies. The main contributions of this research are the argumentive points provided by the experts of Islamic insurance, Shah 'ah scholars and customers in the three countries sampled. The findings reveal changes in insurance principles; similarities in the models practiced and provide justifications in terms of features such as the operator fees and the general harmonization of the models. This study is joined together the application from the operators of Islamic insurance industry; the Ulama of the Shari'ah board and the experts of Islamic insurance industry to meet together to highlight a common model for Islamic insurance, and the best method for surplus (profit or loss) distribution, and other issues. For the Islamic insurance industry, this research can narrow the gap between the current practiced models. This indicates that the proposed Islamic insurance model which is Musharakah- wakalah will increase Islamic operation.